TANGGUNG JAWAB KANTOR JASA PENILAI PUBLIK (KJPP) DALAM MELAKUKAN APPRAISAL (PENILAIAN) ATAS JAMINAN YANG DIGUGAT OLEH KREDITUR - Anindito, Adhitya; Arief Wibisono; Putra Hutomo (Journal of Innovation Research and Knowledge, 2025)
The role of Public Appraisal Firms (Kantor Jasa Penilai Publik/KJPP) in the financial sector, particularly in the valuation of collateral during the credit approval process, is crucial to ensure that the value of the collateralized asset aligns with financing requirements. Appraisals conducted by KJPP must be carried out professionally, objectively, and in accordance with the Indonesian Valuation Standards (Standar Penilaian Indonesia/SPI) and the Indonesian Code of Ethics for Appraisers (Kode Etik Penilai Indonesia/KEPI). However, in practice, legal disputes often arise when creditors feel aggrieved by the valuation results, even though KJPP is, from a legal standpoint, only responsible to the party that formally commissioned the appraisal. This research seeks to answer two main questions: How are the legal implications for creditors regarding the results of collateral appraisals conducted by Public Appraisal Firms (KJPP)? and How is the extent of legal responsibility borne by KJPP in the execution of collateral appraisals? The theoretical framework for this study is grounded in the theory of legal responsibility as articulated by Abdulkadir Muhammad and the theory of collateral law as developed by J. Satrio. The methodology employed is normative juridical research based on legal literature or secondary data, including primary, secondary, and tertiary legal materials. The research approach integrates statutory, conceptual, analytical, and case-based methods. Legal materials were collected by identifying and cataloguing positive legal norms, academic literature, journal articles, and other legal sources. The data were analyzed using systematic and grammatical interpretation, along with analogical legal construction. The findings of this study indicate that KJPP bears legal responsibility solely to the party that lawfully commissions the appraisal and is explicitly designated as the report user in the engagement documentation. As such, creditors who are not directly involved in the appointment of the KJPP lack the legal standing to bring claims. The legal consequences for creditors stemming from appraisal results are limited, except in instances where a valid legal relationship exists and negligence on the part of KJPP can be demonstrably proven. Furthermore, the legal liability of KJPP is limited, proportional, and enforceable only by parties contractually bound to the appraisal engagement, provided that KJPP has performed its duties in accordance with SPI and KEPI. Therefore, in order to achieve legal certainty, all parties intending to rely on the appraisal report—especially creditors—must be formally included in the appraisal engagement and clearly identified as report users.